IR-UWB: An Ultra Low Power Consumption Wireless communication Technologie for WSN - Anouar Darif; Rachid Saadane; Driss Aboutajdine (Institute of Advanced Engineering and Science, 2014)
Wireless Sensor Network (WSN) has gained popularity in recent times in residential, commercial and industrial applications. Several wireless technologies have emerged ranging from short and medium distances. Bluetooth, ZigBee and Impulse Radio Ultra Wide Band (IR-UWB) are three short range wireless communications. There are several features of IR-UWB signals which make them attractive for a short range of wireless applications. Some of the major advantages of IR-UWB are, low complexity, ultra low power consumption, and good time-domain resolution allowing for location and tracking applications. In this paper, we provide a performance study of these popular wireless communication technologies, evaluating the main features and advantages of IR-UWB for WSN in terms of the transmission time and power consumption. We used MiXiM platform under OMNet++ simulator to analyze and evaluate the main features of IR-UWB.